Which Epidemiological Characteristics Drive Decision Making in the Management of Patients with Vestibular Schwannoma - Fík, Zdeněk; Vlasák, Aleš; Zvěřina, Eduard; Sýba, Jaroslav; Lazák, Jan; Peterková, Lenka; Koucký, Vladimír; Betka, Jan (Biomedicines, 2023)
The incidence of sporadic vestibular schwannoma has significantly increased over the past few decades. However, there is no method currently available to accurately predict the risk of subsequent tumor growth. The difference in the management of five patient groups has been evaluated: wait and scan, conversion to microsurgery, conversion to stereoradiotherapy, sterioradiotherapy, and microsurgery. In total, 463 patients with vestibular schwannoma have been consulted in our department from 2010 through 2016. Of the 250 patients initially indicated for observation, 32.4% were later indicated for active treatment. Younger patients were more frequently indicated for surgery (mean age 48 years) compared to older patients, who were more often indicated for stereoradiotherapy (mean age 62 years). Tumor growth was observed more often in patients under 60 years of age and in patients with tumors greater than 10 mm. In elderly patients, including those with larger tumors, a conservative approach is the optimal solution. If tumor growth occurs in the wait-and-scan strategy, it is still possible to continue with a conservative approach in some situations. The duration of follow-up scans is still a matter of debate, as tumors can begin to grow after 5 years from the initial diagnosis.